Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/admt.202200977
|View full text |Cite
|
Sign up to set email alerts
|

Direct Laser Writing of Multishaped VO2 Microactuators Based on Freestanding VO2 Film

Abstract: Microactuators that convert external stimuli such as heat, light, current, and magnetic field into mechanical motion are essential components in microelectro‐mechanical systems. To date, microactuators have been fabricated mainly using conventional microfabrication technologies and inorganic thin films, but although such technologies facilitate the mass production of microdevices, they are expensive and lack flexibility when either preparing only a few devices or facing special needs. Laser‐direct‐writing is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The electrical power applied to structures to ensure the switches was up to an order of magnitude different between the considered studies. Some studies, such as [ 83 ], showed similar deformations regardless of the actuation type. However, in others, for example in [ 80 ], the displacement due to electrical heating was almost ten times smaller than the displacement due to global heating.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The electrical power applied to structures to ensure the switches was up to an order of magnitude different between the considered studies. Some studies, such as [ 83 ], showed similar deformations regardless of the actuation type. However, in others, for example in [ 80 ], the displacement due to electrical heating was almost ten times smaller than the displacement due to global heating.…”
Section: Discussionmentioning
confidence: 99%
“…Good performance was achieved in [ 84 ] by integrating a resistance sensor into the structure itself, which allowed for self-sensing of the actual actuator deformation and using a PID controller to more precisely control the actuator deflection. The highest deformation of 75% [ 83 ] and 60% [ 82 ] corresponded to the smaller devices. In both studies, the devices had a bent shape with a relatively high curvature and flattened, fully or partially, when voltage was applied.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations